Indonesia and The International Refugee Crisis: The Politics of Refugee Protection - Raden Ajeng Rizka Fiani Prabaningtyas (Journal of Indonesian Social Sciences and Humanities, 2019)
This article examines the politics of international refugee protection in Indonesia’s domestic contexts to better understand the discourse of security and protection within the context of Indonesia’s policies and practices in handling refugees This understanding is crucial to find insights relating to the protection gap in the Asia-Pacific region, as Indonesia holds a salient position in advancing the refugee protection regime in the region. Although Indonesia does not seem to employ a specific restrictive asylum and immigration policy as a filtering mechanism to prevent refugee flows from entering their territory, its anxiety and ambivalence to accommodate requests for protection from asylum seekers have characterized its approach towards refugee crises over time. Specifically, this essay analyzed the political discourse and practices in a specific social and political context by historically tracing the experiences of Indonesia in dealing with three refugee crises that took place in the region, namely the Indochinese refugee crisis, the Tampa incident, and the Rohingya humanitarian crisis. It will be argued that the contested discourse and practices of protection in the midst of continuing modulation of insecurity within states are the constitutive factor for the production of state’s approaches to protect refugees. This potentially affected the way states conduct their domestic and foreign policies in the attempt to affirm their national stance towards global refugee phenomena and to avoid greater responsibility without guaranteed cooperative behaviors and solidarity from other counterparts.